Formulating and studying compound chocolate with adding dried grape pomace as a bulking agent - Bursa, Kübra; Kılıçlı, Mahmut; Toker, Ömer Said; Palabıyık, Ibrahim; Gülcü, Mehmet; Yaman, Mustafa; Konar, Nevzat; Yaman, Mustafa (Springer India, 2021)
The use of dried grape pomace (DGP) as a bulking agent for partly substitution of sugar, milk powder and whey powder in compound chocolate (CC) was investigated. D-optimal mixture design was used to determine the effect of composition on the particle size, flow behaviour (Casson yield value and plastic viscosity), as well as total phenolic and resveratrol contents before and after in vitro digestion. The various models (linear, quadratic and cubic) which were identified as significant (P < 0.05) were used in this study. As a result, DGP was found suitable to be used in CC as a bulking agent to partially substitute sucrose, milk powder and whey powder to increase functional properties and decrease the cost of the CC. For CC with the most acceptable rheological properties and a satisfactory level of TPC and resveratrol, optimum usage levels of DGP were identified as 7.1% to 10.0%. Further studies will require to modify flow behaviours by optimizing the particle size of pomace.
Keywords: Grape pomace; Compound chocolate; Functional food; Mixture design; Optimization; ANTIOXIDANT DIETARY FIBER; MILK CHOCOLATE; FLOUR; DIGESTIBILITY; PARAMETERS; DIGESTION; QUALITY; POWDER